2017
DOI: 10.1193/101915eqs154dp
|View full text |Cite
|
Sign up to set email alerts
|

Tests on Thin Reinforced Concrete Walls Subjected to In-Plane and Out-of-Plane Cyclic Loading

Abstract: The present data paper describes an experimental campaign on five thin T-shaped reinforced concrete walls (DOI: 10.6084/m9.figshare.3490754.v2), which includes: details on the test units, materials, test setup, loading protocol, instrumentation, main features of each unit's response, organization of the provided test data, and examples of derived data. The tests aimed at assessing the influence of wall thickness on member stability, the role of lap splices on damage distribution and displacement ductility, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 14 publications
0
32
0
2
Order By: Relevance
“…In the 2010 Chile and 2011 Christchurch earthquakes, out‐of‐plane instability was observed in some slender RC shear walls including L‐shaped walls, which was an uncommon failure mode for concrete walls and raised concerns about the global instability of slender RC walls. The parameters governing the out‐of‐plane failure of RC walls could be obtained by cyclic tensile‐compressive tests on boundary elements and modified with experiments on RC shear walls under in‐plane cyclic loading . Furthermore, relevant analytical models and finite element models for out‐of‐plane instability were developed and subsequently verified with experimental results, demonstrating that these numerical models were able to predict the out‐of‐plane deformation as well as the ultimate failure mode due to out‐of‐plane instability .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 2010 Chile and 2011 Christchurch earthquakes, out‐of‐plane instability was observed in some slender RC shear walls including L‐shaped walls, which was an uncommon failure mode for concrete walls and raised concerns about the global instability of slender RC walls. The parameters governing the out‐of‐plane failure of RC walls could be obtained by cyclic tensile‐compressive tests on boundary elements and modified with experiments on RC shear walls under in‐plane cyclic loading . Furthermore, relevant analytical models and finite element models for out‐of‐plane instability were developed and subsequently verified with experimental results, demonstrating that these numerical models were able to predict the out‐of‐plane deformation as well as the ultimate failure mode due to out‐of‐plane instability .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of bidirectional loading was an additional consideration for the flanged shear walls compared with rectangular walls, as they were designed for acting in different directions. Though both uni‐ and bidirectionally loaded walls had similar strength, it was observed that bidirectional loading resulted in the premature of sudden and substantial losses in strength as well as out‐of‐plane instability for nonplanar RC shear walls …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the influence of lap splices on the in-plane structural behavior was addressed by test units TW2 and TW3. A brief description of the test setup and of the walls response follows; the data of these tests and a more detailed description of the test setup is available in Almeida et al (2017).…”
Section: Description Of Experimental Testsmentioning
confidence: 99%
“…The walls were instrumented using conventional [e.g., linear variable displacement transducer (LVDTs)] and optical measurement systems, a complete description of which can be found in Almeida et al (2017). The deformations of the wall surface were measured using a grid of 29 columns × 18 rows of light-emitting diodes (LEDs) on the east face of the wall, see Fig.…”
Section: (B)mentioning
confidence: 99%